Revisiting mafic dykes of Bornholm : Implications for Baltica in supercontinent Nuna at 1.3 Ga - Luoto, Toni; Salminen, Johanna; Obst, Karsten (Precambrian Research, 2021)
Baltica and Laurentia form the core of the hypothesized Mesoproterozoic supercontinent Nuna in most paleogeographical reconstructions. Long gaps still exist in the Mesoproterozoic paleomagnetic record of Baltica, and different relative configurations for Baltica and Laurentia have been presented. This study presents new paleomagnetic data obtained for mafic dykes on Bornholm (Denmark, southwest Baltica). We provide a new 1.326 +/- 0.010 Ga Bornholm Group I paleomagnetic key pole (Plat: 06 degrees N, Plon: 165 degrees E, K: 21, A95: 6 degrees) for Baltica. This pole supports the low-latitude equatorial core of Nuna at 1.33 Ga, where Kola Peninsula and Northern Norway of Baltica were facing northeastern Greenland of Laurentia. Based on statistically different magnetization directions with Group I and differences in Nb-Zr-Y systematics, we propose a separate Bornholm Group II paleomagnetic pole. This undated, poor-quality pole indicates a paleolatitude of ca. 50 degrees, possibly reflecting an age difference compared to Group I, accompanied with the continental drift. On Bornholm, the wide Listed and Kas dykes of uncertain age yield significantly different paleomagnetic results compared to the other studied dykes there. In addition, the virtual geomagnetic poles (VGPs) of these dykes are 45 degrees apart from each other. On the basis of similar Nb-Zr-Y systematics with the dykes of the 0.98-0.94 Ga Blekinge Dalarna Dolerite Group (Sweden) and overlapping paleomagnetic data with the high-quality 0.95-0.94 Ga paleomagnetic poles of Baltica, an early Neoproterozoic age for the magnetization is proposed. The relatively big discrepancy between Listed and Kas VGPs could stem from an unaveraged paleosecular variation or from a small but significant age difference during rapid plate movements. Peer reviewed